Analisis Kelayakan Pengembangan Alat Evaluasi Kognitif Berbasis Android Pada Program Studi Pendidikan TIK - Isnania Lestari; Sandrawati Sandrawati (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The evaluation stage is the final stage in the learning process. Currently, the evaluation process is still using the manual method. Based on this, an application was developed as an android-based cognitive evaluation tool at the Information and Computer Technology Education Study Program (PTIK) IKIP PGRI Pontianak. The purpose of this study was to analyze the feasibility of developing an android-based cognitive evaluation tool and also student responses after using an android-based cognitive evaluation tool in the ICT Education Study Program of IKIP PGRI Pontianak. The development method used is Research and Development (RD) research with the ADDIE model. The research subjects in the study consisted of development subjects involving three media experts and product trial subjects involving 10 students as small-scale test subjects and 42 students as large-scale trial subjects. Data collection using closed questionnaires, and Data analysis apply descriptive quantitative analysis. The results of the media expert test obtained a score of 90.3%, including the Very Eligible category. Small-scale trials obtained a score of 76% in the Eligible category. Large-scale trials obtained a score of 81% in the Very Eligible category. The response results obtained are very good, because they have fulfilled the aspects needed in making the application.